The Sociology of Ritual and Resistance: Constructing Religious Educational Meaning in the Marginal Spaces of Pastoral Care - Teresia Noiman Derung; Bernadeta Sri Jumilah; Rosalia Ina Kii; Andri Fransiskus Gultom (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2025)
This article examines the sociological reconceptualization of religious education within the marginal spaces of pastoral care through the lens of the dialectic of ritual and resistance. Previous studies on pastoral care have tended to frame ritual either theologically or psychologically, neglecting how structural inequality, class marginality, institutional exclusion, and power asymmetries shape the production of meaning in religious education. Employing a qualitative case study in three urban pastoral communities in Indonesia, this research utilizes participant observation and in-depth interviews with 34 pastoral actors (clergy, lay volunteers, and marginal parishioners). Data analysis was conducted through thematic analysis guided by an abductive logic, moving iteratively between empirical data and the framework of the sociology of ritual. The findings demonstrate that ritual operates as a double-edged mechanism: reproducing hegemonic narratives while simultaneously providing a tactical space for marginal actors to enact subversion through embodied performance, vernacular reinterpretation, and collective improvisation. This dialectic gives rise to what we formulate as "threshold pedagogy," an articulated form of vernacular theology emerging from structural vulnerability rather than merely a localized pedagogical strategy or hidden curriculum. This pedagogy functions as a meaning-making practice through which marginal groups actively negotiate, disrupt, and appropriate dominant narratives via their ritual participation. The novelty of this study lies in its explicit integration of the sociology of ritual and pastoral care studies, challenging Durkheimian functionalism by positioning conflict and agency as constitutive elements of religious education in liminal spaces. Methodologically, this research offers a grounded framework for analyzing religious education as a contested social practice while paving the way for structure-sensitive and participatory pastoral interventions.